Physical Fitness Index of Non-Vegetarian and Lacto-Vegetarian Adults: A Comparative Study of Harvard Step Test (Nepal Medical College Journal, 2020)
A pure vegetarian, consumes the food of plant origin, reportedly has lower risk of chronic diseases and may have enhanced athletic performance compared to omnivorous. Lacto-vegetarian consumes dairy products and plant-based foods where as lacto-ovo-vegetarians, being categorized as vegetarian, consumes egg as well. Considering vegan diet as healthy food habit and appropriate medication, world is directing towards vegan diet. Lacto-vegetarian and non-vegetarian participants were included in this study based on inclusion criteria from various streams; MBBS, BDS, CTEVT and a randomized cross-sectional study was performed among selected students and independent sample ‘t’ was used for analysis. Total enrolled participants (n=100), lacto-vegetarians (LV=50, male= 15, female=35) group and non-vegetarians (NV=50, male= 22, female=28) group were separated, age 16-27 years. Comparing the variables, result showed (NV=18.28±2.09, LV=19.14±1.43yrs, P=0.01), weight (NV=53.76±9.02, LV=50.16±4.82kg, P=0.01) and BMI (NV=29.63±4.49, LV=28.03±2.52kg/m2, P=0.03). Lacto-vegetarians reported greater exercise duration (NV=224.24± 52.13s, LV=248.50±42.33s, P=0.01) and physical fitness index score (NV=62.14±14.86, LV=72.41±16.80, P=0.002) which was statistically significantly. Waist circumference (77.32±4.22, 70.48±3.95, P=0.00), hip circumference (86.97±3.7, 81.76±5.65, P=0.00), waist hip ratio (0.88 ±0.04, 0.86±0.05, P=0.01), exercise duration (263.51±43.5, 220.43±44.76) and physical fitness index score (74.03±14.42, 63.3±16.61) were significantly greater in male (n=37) than female (n=63). The present study concludes, lacto-vegetarians are physically fit compared to non-vegetarian so as male compared to female.